DESIGNING AND VALIDATION OF A VIDEO BASED INSTRUCTIONAL DEVICE (CD-ROM) ON ABORTION IN DAIRY ANIMALS - SHARMA, MK; VERMA, HK; KANSAL, SK; BRAR, PS (The Indian Journal of Animal Reproduction, 2016)
A video based CD-ROM on abortion in dairy animals was designed and its appropriateness as an instructional device was validated. The CD-ROM was prepared by developing a manuscript containing all the relevant information about abortion in dairy animals and the multimedia elements viz. text, stills/photographs, videos and audio. The developed device was presented to 20 subject matter experts for the validation of multimedia elements and the attributes of the developed CD-ROM. Mean score of 3.74/4.00 was assigned to multimedia elements and the final rating score of the attributes of CD-ROM was 3.87/4.00. After exposure to CD-ROM, the respondents had enhancement in their knowledge level. In brief, the CD-ROM on abortion in dairy animals was appropriate and valid instructional device for the dissemination of relevant information to end user.
Keywords: Abortion; CD-ROM; Dairy animal; Validation; Video